ON ONE PROBLEM OF THE DYNAMIC OPTIMIZATION - Apinian, A. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
The present paper is devoted to the study of optimal control of pollution. It’s assumed that the variable of stock of pollution is included into the utility function. The algorithm of the evaluation of optimal solution is given. The algorithm is based on the method of random search.
Keywords: optimal control of pollution; utility function; method of random search